2019
DOI: 10.1111/ibi.12794
|View full text |Cite
|
Sign up to set email alerts
|

Individual–resource networks reveal distinct fruit preferences of selective individuals from a generalist population of the Helmeted Manakin

Abstract: Ecological studies traditionally assume that generalist populations are homogeneous in the use of food resources, but empirical evidence supports that intraspecific differences in morphology, physiology and behaviour affect foraging decisions and promote diet variation among individuals. Furthermore, the temporal availability of resources may shape the dynamics of population trophic niche, which ultimately depends on individual niches. In this study, we investigated the seasonal changes in individual‐based net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…The importance of density-dependence is well established in the seed dispersal literature, mainly focusing on the effects of temporal changes in food availability 2,3,45 . We and recent studies 7,46 have found that the temporal availability of fruit influences frugivore choices, which in turn causes intraspecific variation in seed dispersal parameters. Intraspecific variability in both plants and animals does not simply add noise to systems, but alters dispersal processes and patterns with consequences for plant demography, communities, evolution and responses to anthropogenic changes; by reducing this variability to an average value, important details on the seed dispersal capacity and resilience of animals has been lost [5][6][7]46 .…”
Section: Vitis Flexuosamentioning
confidence: 75%
See 1 more Smart Citation
“…The importance of density-dependence is well established in the seed dispersal literature, mainly focusing on the effects of temporal changes in food availability 2,3,45 . We and recent studies 7,46 have found that the temporal availability of fruit influences frugivore choices, which in turn causes intraspecific variation in seed dispersal parameters. Intraspecific variability in both plants and animals does not simply add noise to systems, but alters dispersal processes and patterns with consequences for plant demography, communities, evolution and responses to anthropogenic changes; by reducing this variability to an average value, important details on the seed dispersal capacity and resilience of animals has been lost [5][6][7]46 .…”
Section: Vitis Flexuosamentioning
confidence: 75%
“…We and recent studies 7,46 have found that the temporal availability of fruit influences frugivore choices, which in turn causes intraspecific variation in seed dispersal parameters. Intraspecific variability in both plants and animals does not simply add noise to systems, but alters dispersal processes and patterns with consequences for plant demography, communities, evolution and responses to anthropogenic changes; by reducing this variability to an average value, important details on the seed dispersal capacity and resilience of animals has been lost [5][6][7]46 . Individuals within a population respond to fruit abundance, which might alter the extent and direction of intraspecific variation within populations.…”
Section: Vitis Flexuosamentioning
confidence: 75%
“…It is possible that this disparity reflects interannual variation in fruit availability, which has been documented at our study site [39,68]. However, variation in resource use at the community and population levels may also be the result of distinct preferences among individuals, which have been observed to vary seasonally in some cases [89,90]. Thus, the high degree of variation in our estimates of diet, as well as variation among years may indicate the influence of individual preferences and possibly resource partitioning among individuals.…”
Section: Seasonal Changes In Dietmentioning
confidence: 86%
“…Antilophia galeata consumes fruits mainly during fl ight (Marini 1992, Silva & Melo 2011, Pires & Melo 2019. Flight maneuvers often wear out the wings by putting them in more contact with the environment, suff ering the infl uence of stressors that makes it diffi cult to stabilize the character (Gonçalves & Melo 2012).…”
Section: Discussionmentioning
confidence: 99%